Chemotherapeutic effects of doxorubicin loaded PEG coated TiO nanocarriers on breast cancer cell lines - Tas, Ayca; Kekliklicioglu Cakmak, Nese; Gumus, Erkan; Atabey, Mustafa; Silig, Yavuz (Annals of Medical Research, 2021)
None
Keywords: Breast Cancer; MDA-MB-231; TiO-PEG-DOX: DOX.